Effects of Whey Protein Isolate on Black Pepper Essential Oil Ultrasound-Assisted Emulsion on Physical Characteristics, Antioxidant Activity, and Antibacterial Properties (Faculty of Animal Science Universitas Brawijaya, 2022)
The purpose of this research was to determine the best ratio of whey protein isolate (WPI) for encapsulation of black pepper (Piper nigrum) essential oil (BPEO) on ultrasound-assisted emulsion. O/W emulsion was made from the oil phase from BPEO and corn oil (30:70) and the aqueous phase was made from the liquid modified glucomannan. The effect of WPI was investigated at different ratios (T0= 0%, T1= 2%, T2= 4%, T3= 6%,). BPEO emulsion was prepared using an ultrasonication method with the intention for produce nanoemulsion. The method of this research was an experiment with a Completely Randomized Design (CRD) by using four treatments and three replications, then continued by Duncan Multiple Range Test (DMRT). The physical characteristics were observed by viscosity and optical microscope. DPPH scavenging activity was used to know the effect of encapsulation on antioxidant activities. The Antibacterial activity was evaluated by the Kirby Bauer method with E. coli as the pathogen bacteria and L. casei as the probiotic bacteria. The increase ratio of WPI influences morphology. Different ratio of WPI gave a highly significant effects (p<0.01) on the viscosity and antioxidant, and gave no significant effects (p>0.05) on the inhibition diameter zone for E. coli and L. casei. Based on its physical characteristic, antioxidant activity, and antibacterial properties, it can be concluded that WPI can protect the BPEO by stabilizing O/W emulsion and may have the potential to be used as an alternative natural antioxidant and antibacterial additive in many food applications.